Recoveries of grey seals (Halichoerus grypus) tagged on the Murman coast in Russia - Henriksen, Gunnar; Haug, Tore; Kondakov, Andrej; Nilssen, Kjell Tormod; Øritsland, Torger (NAMMCO Scientific Publications, 2007)
A total of 612 grey seal (Halichoerus grypus) pups were tagged on the Murman coast, Russia, in the years 1991, 1992 and 1994. A majority of them (542) were tagged at the Ainov archipelago. Thirty-one (2.9%) of the tagged seals have been recovered, mainly (77%) as bycatches in fishing gear. The majority of recaptures (74%) were made during the first year after tagging, while the oldest recaptured seal was 10 years old. Only 1 recapture, at Ainov, was made in the area were the seals had been tagged, otherwise distances between tagging and recaptures varied from less than 100 km to more than 1,000 km. All recaptures were made north of 68°N.